Effectiveness of Ramania Leaves (Bouea macrophylla Griffith) from South Kalimantan as a Mosquito Larvae Biolarvicidal - Aryzki, Saftia; Febrianti, Dwi Rizki (Fakultas Kedokteran Universitas Lambung Mangkurat, 2023)
Indonesia itself as a tropical country has many plants that can be used as biolarvicides, one of which is the ramania plant (Bouea macrophylla Griffith). Ramania fruit epidermis contains secondary metabolites such as flavonoids, saponins, phenolic tannins, alcohol, steroids and terpenoids where these compounds have a larvicidal effect. The purpose of this study was to determine the activity of the ethanol extract of the epidermis of the ramania fruit as a biolarvicidal Mosquito larvae from the LC50 value. This research is a laboratory experimental research. The treatment concentrations used in this study were 25 ppm, 50 ppm, and 100 ppm. Temephos 1% was used as a positive control. Concentrations were then tested on 20 larvae instar III. The results of SPSS analysis with a significance of <0.05 showed that there was an effect of treatment on the number of larvae deaths, where the results of Tuckey analysis showed that concentrations of 50 ppm and 100 ppm and Temephos 1% showed differences. which means the number of deaths of test larvae. The results showed that the ethanol extract of ramania rind of ramania fruit (Bouea macrophylla Griffith) was effective as a biolarvicidal mosquito larvae. The results of probit analysis showed that the LC50 of ethanol extract of ramania rind against larvae was 20,844 ppm which is a low toxic group in aquatic environments.